Female Trustees and University Financial Performance - Lenard, Mary Jane; York, E. Anne; Yu, Bing (International Journal of Economics and Financial Issues, 2019)
The board of trustees of a postsecondary educational institution has a similar role to a corporate board of directors. Trustees must represent stakeholder interests, have a role in governance, and are responsible for the continued financial success of the institution (Brown, 2014). The composition of the board is an important factor in university governance, just as it is in a corporation. Previous research has found that female board members do have an impact on the financial performance of their corporations. We apply that analysis to private, nonprofit colleges and universities and examine whether the gender composition of the board of trustees affects the financial performance of their institutions. Our results indicate that a higher percentage of women on the board of trustees increases the likelihood of having a passing financial responsibility composite score, as measured by the U.S. Department of Education. Keywords: Gender Diversity, Trustees, University Boards, Financial Performance JEL Classifications: L31, I23 DOI: https://doi.org/10.32479/ijefi.8518